Midwifery Care For Maternal Mother Ny: W P: 1 A: 0 With Placenta Retention At The Vivi Rahayu Am.Keb Midwifery Clinic, Kota Madya Tanjung Balai - Delimayani (International Journal on Health and Medical Sciences, 2022)
Maternal death or death of pregnant women is the death of a woman while pregnant, giving birth or within 42 days after giving birth (wikipedia). Meanwhile, according to Dr. Karlina Sari Maternal death is when a woman dies due to something related to pregnancy, childbirth and 42 days after giving birth Maternal death is the death of a woman during pregnancy or within 24 days after the end of the pregnancy due to any cause, regardless of the age of the pregnancy and the actions taken to end the pregnancy. According to WHO, there are several causes of maternal death, namely postnatal bleeding, high blood pressure. , complications in childbirth and unsafe abortions. Complications in childbirth that are not handled properly and on time can cause maternal death, around 15% of pregnancies/deliveries experience complications and 85% are normal, one of the complications in childbirth is retained placenta, according to the editorial article by healthy doctors, retained placenta is retained the placent is in the uterus and does not come out by itself naturally or up to 1 hour after the birth of the baby the placenta has not come out.